The letters of Oscar Hammerstein II - Hammerstein, Oscar 1895-1960 (2022)
The Letters of Oscar Hammerstein II is a collection of hundreds of letters to and from and the man who all but invented the modern Broadway musical. Best remembered for Show Boat, Oklahoma!, Carousel, South Pacific, The King and I, Cinderella, and The Sound of Music, Hammerstein was a lyricist, librettist, and producer-not only on Broadway, but also in Hollywood, London, and on television. The letters deal with all aspects of show business. Oscar's correspondents included Edna Ferber, Arthur Freed, Judy Holliday, Jerome Kern, Gertrude Lawrence, Josh Logan, General Douglas MacArthur, Mary Martin, James Michener, Basil Rathbone, Richard Rodgers, Billy Rose, Stephen Sondheim, John Steinbeck, and Florenz Ziegfeld. The letters are funny, revealing, touching, and surprising. There are passionate love letters, friendly and witty letters, angry and conciliatory letters-all of them exquisitely written. His correspondence is also a mirror of his times, reflecting the challenges of race and prejudice, war and peace
Includes Includes bibliographical references and index
Table of Contents: Introduction - Notes on the Letters - Acknowledgments - Chapter One:1917 through 1929 - Chapter Two:1930 through 1936 - Chapter Three:1937 through 1939 - Chapter Four:June 1941 through 1942 - Chapter Five:1943 - Chapter Six:1944 - Chapter Seven:1945 (and Smatterings from 1946 and 1947) - Chapter Eight:1949 (Preceded by a Smattering of Letters from 1948) - Chapter Nine:1950 - Chapter Ten:1951 - Chapter Eleven:1952 - Chapter Twelve:1953 - Chapter Thirteen:1954 - Chapter Fourteen:1955 - Chapter Fifteen:1956 - Chapter Sixteen:1957 - Chapter Seventeen:1958 - Chapter Eighteen:1959 - Chapter Nineteen:1960 - Permissions Acknowledgments - Index
Keywords: Hammerstein, Oscar -- 1895-1960; Geschichte 1917-1960; Musicals--writing and publishing; Musicals; Music / 20th century; Songwriter; Librettist; Musikproduzent; USA; Briefsammlung